Co‐occurrence of Proteus syndrome and ventricular tachycardia cardiac arrest in a teenager. Issue 5 (20th February 2023) - Ferguson, Richard; Scurr, Ingrid; Ours, Christopher A.; Johnston, Jennifer J.; Pike, Katharine; Spentzou, Georgia
Abstract: Proteus syndrome is an extremely rare overgrowth condition caused by a somatic variant of the AKT1 gene. It can involve multiple organ systems though rarely is there symptomatic cardiac involvement. Fatty infiltration of the myocardium has been described but has not been reported to cause functional or conduction abnormalities. We present an individual with Proteus syndrome who suffered a sudden cardiac arrest.